Improving Robot Motor Learning with Negatively Valenced Reinforcement Signals - Navarro-Guerrero, Nicolás; Lowe, Robert J.; Wermter, Stefan (Frontiers in Neurorobotics, 2017)
Both nociception and punishment signals have been used in robotics. However, the potential for using these negatively valenced types of reinforcement learning signals for robot learning has not been exploited in detail yet. Nociceptive signals are primarily used as triggers of preprogrammed action sequences. Punishment signals are typically disembodied, i.e. with no or little relation to the agent-intrinsic limitations and they are often used to impose behavioural constraints. Here, we provide an alternative approach for nociceptive signals as drivers of learning rather than simple triggers of preprogrammed behaviour. Explicitly, we use nociception to expand the state space while we use punishment as a negative reinforcement learning signal. We compare the performance -- in terms of task error, the amount of perceived nociception and length of learned action sequences -- of different neural networks imbued with punishment-based reinforcement signals for inverse kinematic learning. We contrast the performance of a version of the neural network that receives nociceptive inputs to that without such a process. Furthermore, we provide evidence that nociception can improve learning making the algorithm more robust against network initializations as well as behavioural performance by reducing the task error, perceived nociception and length of learned action sequences. Moreover, we provide evidence that punishment, at least as typically used within reinforcement learning applications may be detrimental in all relevant metrics.